Plant genetic resources and germplasm use in India - Bonham CA; Dulloo, Mohammad Ehsan; Mathur, P.N.; Brahmi, P.; Tyagi, V.; Tyagi, R.K.; Upadhyaya, Hari D. (2010)
Plant genetic resource (PGR) scientists now recognize the importance of shifting from a singular focus on conservation to a focus on both conservation and utilization of germplasm in order to meet future challenges. This paper analyzes the patterns of distribution of pearl millet, six small millets, chickpea and pigeonpea germplasm over the last 10 years at the two major genebanks functioning in India: the National Genebank at the National Bureau of Plant Genetic Resources (NBPGR) and a Consultative Group for International Agricultural Research (CGIAR) Genebank at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), as well as the patterns of use of germplasm by millet breeders in India. Between the years of 1999-2009, ICRISAT distributed approximately 48 per cent of all its collections to breeders in India whereas NBPGR distributed 36 per cent of their collection. A total of 20 responses (30 per cent of surveys sent) were collected through this study. Sixty-five percent of respondents said that they rarely (<50 per cent of the time) use germplasm from genebanks in their breeding programs. It is important that both genebanks look into several issues in order to improve levels of distribution and utilization, collection, duplication, engagement of the private sector, access to information, and pre-breeding.